Leveraging Social Media Data Analytics for Tourism Marketing Policies in West Java, Indonesia - Yusuf Abdullah; Asep Miftahuddin; Rispiaga Rispiaga; Deni Mulyana; Isbandi Isbandi (Jurnal Manajemen Pelayanan Publik, 2023)
After the government failed to release updated data on the handling of COVID-19, the status of the pandemic in Indonesia has been declared to have ended and transitioned into an endemic disease. This policy has received various responses from the public, including the tourism sector. Therefore, the objective of this research is to gain a comprehensive understanding of the public perception regarding the issue of tourism during the endemic period by examining how people communicate through social media, particularly Twitter. The research method employed is the collection of Twitter conversations from February 2nd, 2023, at 12:00 PM WIB until March 30th, 2023, at 11:59 PM WIB using the DEA (Data Envelopment Analysis) system through Twitter's API (Application Programming Interface). The research findings indicate that out of a total of 1823 analyzed tweets, 77% of them demonstrate a positive sentiment towards tourism, while 17% or 394 tweets exhibit a negative sentiment, and only 6% or 140 tweets show a neutral sentiment. These findings present opportunities for the West Java provincial government to utilize Twitter as a valuable source of information for decision-making and policy evaluation during the endemic period.